Nilai-Nilai Tradisi Hapolas dan Relefansinya Dalam Pempelajaran Bahasa dan Sastra Indonsia - Ilham, Hania; Ahmad, Idrus; Djais, Idwan (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to describe and analyze hapolas cultural values ​​and how they are implemented in learning Indonesian language and literature. Data collection techniques were carried out through documentation techniques in the form of event records and interview techniques to obtain information about the traditional values ​​of hapolas. The data analysis technique is carried out by examining phenomena or events as a whole. Grouping and categorizing data into predetermined aspects, the results of the grouping are connected with other data to obtain the truth. The data collected was analyzed according to the research objectives. In this research, it was found that the hapolas tradition of the Ngofakiha community in East Makian District is carried out by collecting money voluntarily to help ease the burden on people mourning the death of a family member. They carry out a series of dina/tahlilan activities from the first day to the ninth day which involve many people, causing costs, so on the tenth day the hapolas tradition is carried out to voluntarily help lighten this burden. Therefore, the hapolas tradition has the following values: spiritual, friendship, social, entertainment and cooperation values ​​that describe the identity of members of the East Makean community.